2008
DOI: 10.1093/nar/gkn919
|View full text |Cite
|
Sign up to set email alerts
|

Metastases suppressor NM23-H2 interaction with G-quadruplex DNA within c-MYC promoter nuclease hypersensitive element induces c-MYC expression

Abstract: Regulatory influence of the G-quadruplex or G4 motif present within the nuclease hypersensitive element (NHE) in the promoter of c-MYC has been noted. On the other hand, association of NM23-H2 to the NHE leads to c-MYC activation. Therefore, NM23-H2 interaction with the G4 motif within the c-MYC NHE presents an interesting mechanistic possibility. Herein, using luciferase reporter assay and chromatin immunoprecipitation we show NM23-H2 mediated c-MYC activation involves NM23-H2-G4 motif binding within the c-MY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
181
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(187 citation statements)
references
References 64 publications
(81 reference statements)
6
181
0
Order By: Relevance
“…NME2 regulates MYC transcription by binding to the nuclease hypersensitive element III (NHE III) region of the MYC promoter close to the transcription start site (35)(36)(37). Given the mode of action of stauprimide, we hypothesized that cancer cells with different genomic regulatory sequences around the NHE III region may respond differently to stauprimide.…”
Section: Resultsmentioning
confidence: 99%
“…NME2 regulates MYC transcription by binding to the nuclease hypersensitive element III (NHE III) region of the MYC promoter close to the transcription start site (35)(36)(37). Given the mode of action of stauprimide, we hypothesized that cancer cells with different genomic regulatory sequences around the NHE III region may respond differently to stauprimide.…”
Section: Resultsmentioning
confidence: 99%
“…These higher order structures are four-stranded intramolecular foldings of single-stranded DNA, formed by the stacking of two or more tetrads, each comprising four guanines connected by Hoogsteen hydrogen bonds and stabilized with monovalent cations. G4s are globular in nature, analogous to the tertiary structure of a protein, and they serve as the silencer element for MYC transcription, putatively through sequestration of transcriptional factor binding sites (33)(34)(35).In the present study we identified the ellipticine derivative GQC-05 (NSC338258) as a potent and selective stabilizer of the MYC G4 structure. We demonstrate that the activity of this compound is dependent on the presence and regulation of a G4 within the MYC promoter region and that it specifically modulates protein binding to the NHE III 1 .…”
mentioning
confidence: 75%
“…Nm23-H2 also binds to c-myc and NHE have a G4 motif that withhold c-myc expression and Nm23-H2 act as an activator of c-myc expression and there is decrease levels of Nm23-H2 leads to lower c-myc levels (Simonsson et al, 2000;Siddiqui-Jain et al, 2002). The decreased expression of Nm23-H2 are associated with metastatic potential and reduction in Nm23-H2 level in cancer cells reduced in c-myc expression that decreases apoptosis of the cancer cells enhancing metastasis (Zajac-Kaye, 2001;Thakur et al, 2009). Nm23-H5 involves in nucleotide metabolism of the germ cells which are expressed in testis close similar to Nm23-H1, H2, H3 and H4 depending upon the type of the tissue.…”
Section: Differential Expression Of Nm23 Gene Family and Regulationmentioning
confidence: 99%